Quizizz Learning Media Innovation on Math Learning Outcomes: Inovasi Media Pembelajaran Quizizz Pada Hasil Belajar Matematika - Hikmah, Noviatul; Supriadi, Edi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Elementary mathematics education plays a crucial role in developing students’ logical reasoning and problem-solving skills. Specific Background: However, conventional teaching methods often fail to engage students, especially in topics like plane geometry, leading to low learning outcomes. Knowledge Gap: While previous studies have explored digital learning tools, limited research addresses the use of Quizizz in lower-grade primary contexts using offline barcode-based quizzes. Aims: This study aimed to examine the effect of Quizizz as an innovative learning medium on third-grade students’ mathematics achievement in the topic of plane shapes. Results: A quasi-experimental method was employed, involving 60 students divided into control and experimental groups. Results showed significant improvements in the experimental group, with t-test values (p < 0.05) and a regression analysis indicating Quizizz accounted for 20.5% of the variance in outcomes. Novelty: The integration of barcode-based Quizizz without the need for student-owned devices presents an accessible and inclusive approach in low-digital-access environments. Implications: These findings underscore the effectiveness of gamified digital tools like Quizizz in enhancing mathematical understanding and align with the Merdeka Belajar curriculum’s push for ICT integration in education.Highlight : The use of Quizizz significantly improves mathematics learning outcomes for third-grade students. The test items and questionnaires used were proven valid and reliable, ensuring accurate data collection. Quizizz supports active and interactive learning, aligned with the Merdeka Curriculum principles. Keywords : Quizizz, Learning Outcomes, Mathematics, Learning Media, Plane Figures